1995
DOI: 10.2337/diacare.18.8.1104
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Factors Determining Diabetes and Impaired Glucose Tolerance: A 20-year follow-up of the Finnish and Dutch cohorts of the Seven Countries Study

Abstract: Although the regression coefficients were in general not very large, these results indicate that a high intake of fat, especially that of saturated fatty acids, contributes to the risk of glucose intolerance and NIDDM. Foods such as fish, potatoes, vegetables, and legumes may have a protective effect. In addition, the observed inverse association between vitamin C and glucose intolerance suggests that antioxidants may also play a role in the development of derangements in glucose metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
269
6
5

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 437 publications
(304 citation statements)
references
References 0 publications
20
269
6
5
Order By: Relevance
“…Although the controversy in earlier data concerning marine fatty acids and glucose metabolism (Salomaa et al, 1990;Feskens et al, 1991Feskens et al, , 1995Borkman et al, 1993;Adler et al, 1994;Vessby et al, 1994aVessby et al, , b, 2001Pan et al, 1995;Marshall et al, 1997;Baur et al, 1998;Gustafsson et al, 1998;Bjerregaard et al, 2000;Ekblond et al, 2000;Mori et al, 2000;Hu et al, 2001;Salmeró n et al, 2001;Dewailly et al, 2001a, b;van Dam et al, 2002;Wang et al, 2003;Harding et al, 2004;Thorsdottir et al, 2004) may be partly explained by different doses and durations of supplementation in intervention studies, and by different background diets between the study populations, inclusion of subjects with different PPARG Pro12Ala genotypes could also influence the outcome of the study. That PPARG genotype may affect the associations of dietary fat composition with insulin concentrations (Luan et al, 2001) and serum triacylglycerol response to fish oil supplementation (Lindi et al, 2003) was suggested previously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the controversy in earlier data concerning marine fatty acids and glucose metabolism (Salomaa et al, 1990;Feskens et al, 1991Feskens et al, , 1995Borkman et al, 1993;Adler et al, 1994;Vessby et al, 1994aVessby et al, , b, 2001Pan et al, 1995;Marshall et al, 1997;Baur et al, 1998;Gustafsson et al, 1998;Bjerregaard et al, 2000;Ekblond et al, 2000;Mori et al, 2000;Hu et al, 2001;Salmeró n et al, 2001;Dewailly et al, 2001a, b;van Dam et al, 2002;Wang et al, 2003;Harding et al, 2004;Thorsdottir et al, 2004) may be partly explained by different doses and durations of supplementation in intervention studies, and by different background diets between the study populations, inclusion of subjects with different PPARG Pro12Ala genotypes could also influence the outcome of the study. That PPARG genotype may affect the associations of dietary fat composition with insulin concentrations (Luan et al, 2001) and serum triacylglycerol response to fish oil supplementation (Lindi et al, 2003) was suggested previously.…”
Section: Discussionmentioning
confidence: 99%
“…Especially, long-chain nÀ3 polyunsaturated fatty acids have been found to be associated with enhanced glucose metabolism (Feskens et al, 1991;Adler et al, 1994;Feskens et al, 1995;Baur et al, 1998;Ekblond et al, 2000;Hu et al, 2001;Salmeró n et al, 2001;Thorsdottir et al, 2004) and to lower serum free fatty acid (FFA) concentrations (Gustafsson et al, 1998), although there are also contradictory results (Salomaa et al, 1990;Borkman et al, 1993;Vessby et al, 1994aVessby et al, , b, 2001Pan et al, 1995;Marshall et al, 1997;Bjerregaard et al, 2000;Mori et al, 2000;Dewailly et al, 2001a, b;van Dam et al, 2002;Wang et al, 2003;Harding et al, 2004). It is not known whether some of the discrepancies in previous results could be attributed to differences in the genetic background of the subjects.…”
Section: Introductionmentioning
confidence: 99%
“…A low-risk diet was defined as a diet low in trans fat, glycemic load, high in cereal fiber and polyunsaturated to saturated fat ratio. This latest study adds to the body of literature linking the role of diet as a risk factor for the development of diabetes (Jenkins et al, 1988;Salmeron et al, 1997;Munoz et al, 1979;Feskens et al, 1991Feskens et al, , 1995Williams et al, 1999).…”
Section: Discussionmentioning
confidence: 89%
“…In particular, among Hong Kong Chinese, the prevalence appears to be rising (Cockram et al, 1993;Janus et al, 2000), the latest figures for 1995 for men and women being 2.0 and 1.4% for those aged 25 -34 to 21.7 and 29.3% at age 65 -74 y. Dietary factors have been shown to contribute to the development of glucose intolerance. Thus foods with high glycemic index (Jenkins et al, 1988;Salmeron et al, 1997), low dietary fibre (Salmeron et al, 1997;Munoz et al, 1979), carbohydrate-rich foods, excessive energy intake (Feskens et al, 1991), and high fat intake (particularly saturated fats; Feskens et al, 1995) may predispose to glucose intolerance. On the other hand, high intakes of fish, potato, vegetable, legume and vitamin C are inversely associated with the development of diabetes mellitus (Feskens et al, 1995;Williams et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation